The Factor Analysis of Problems of Rural Waste Management in Qazvin Township - Parvaneh Safari Alamouti; Ali Shams (Rāhburdhā-yi tusi̒ah-i rūstāyī, 2016)
The descriptive- survey research was conducted to evaluate the rural waste management problems in Qazvin Township. The statistical population was consisted of all rural households in Qazvin Township (N=31338) which were selected and studied base on Cochran sampling formula and using randomized multi-stage sampling method 464. The research tool was a researcher made questionnaire. In this field, the content and face validity was verified by an expert panel. The reliability of research tool was acquired by conducting a pilot study and calculation cronbach alpha coefficient equals to 0.9. Data were analyzed by SPSS/Win 18 software and exploratory factor analysis technique was used. The results revealed that six factors named as final disposal problem of household waste management (17/11 percent), educational and cultural problems of household waste (14/11 percent), health problems of household waste (12/11 percent), knowledge and health problems of agricultural wastes (8/98 percent), knowledge problem of household waste (6/99 percent),  and education problem of agricultural waste (5/47 percent) were explained as 64.68 percent of total waste problems in the region.